Aktualisasi Perlindungan Data Pribadi Konsumen Terhadap Penggunaan Layanan Internet - Trisetyo, Muhammad Dhimas; Agustianto, Agustianto; Sudirman, Lu (Jurnal Bedah Hukum, 2025)
The use of internet services has become widespread and has become an integral part of daily life for millions of individuals around the world. However, in accessing and using internet services, consumers often face various risks and challenges, such as privacy violations, online fraud, or non-compliance with promises made by service providers. Apart from that, a high security system also increases public confidence in comprehensive data security protection. Legal protection aims to integrate and coordinate various interests in society because in one movement of interests, protection of certain interests. In implementing personal protection in electronic systems, it must be based on the principle of respect for personal data as privacy and every owner of personal data has the right to data in the electronic system. Therefore, legal protection of consumers regarding the use of internet services is becoming increasingly important. This research actualizes the protection of consumer personal data in the context of internet service use. We analyze relevant legal and regulatory developments, both at national and international levels, that play a role in protecting consumer rights and interests in the digital ecosystem.